Il potenziamento cognitivo tra etica, deontologia e diritti (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Human enhancement raises many ethical, deontological and legal issues. However, the Italian Code of Medical Deontology has recognized its practicability, dedicating a specific rule to it (article 76). This decision has been widely discussed also in consideration of its non-compatibility with some European documents and with the Italian legal system. In this context, it is necessary to provide proper insights into this topic, because of its worrying consequences on an individual and social level. It is therefore claimed an interpretation abrogating article 76 of the Code of Medical Deontology, waiting for an abolition of this article by the National Federation of Doctors Orders Surgeons and Dentists.
Keywords: Human enhancement; artificially intelligent; moral or cognitive enhancement; genome editing; deontological rules